Testing Emotional Vulnerability to Threat in Adults Using a Virtual Reality Paradigm of Fear Associated With Autonomic Variables - Brandão, Marcus L.; Nobre, Manoel Jorge; Estevão, Ruth (Frontiers in Psychiatry, 2022)
Fear and anxiety are generally assessed as responses of prey to high or low levels of threatening environments, fear-conditioned or unconditioned stimuli, or the intensity and distance between predator and prey. Depending on whether a threat is close to or distant from the individual, the individual exhibits specific behaviors, such as being quiet (freezing in animals) if the threat is distant or fleeing if the threat is close. In a seminal paper in 2007, Dean Mobbs developed an active prevention virtual reality paradigm (VRP) to study a threat’s spatial imminence using finger shocks. In the present study, we used a modified VRP with a distinctive feature, namely a dynamic threat-of-loud noise paradigm. The results showed a significant reduction of the number of times the subjects were captured in the high predator phase (85 dB) vs. control phases, suggesting that the participants were motivated to avoid the high predator. Concomitant with avoidance behavior, a decrease in respiratory rate and an increase in heart rate characterized the defense reaction. These results demonstrate behavioral and autonomic effects of threat intensity in volunteers during a VRP, revealing a profile of defense reaction that reflects the individual emotional susceptibility to the development of anxiety.